Daur Ulang Air Leri Dalam Mengurangi Limbah Rumah Tangga (Fakultas Teknik, Universitas Brawijaya, 2025)
Household waste consists of various types, one of which is rice washing water. Rice washing water has many benefits that can be used for everyday life. The community of RT 02 RW 03 Ngadilangkung Village, Kepanjen District, Malang Regency is a community that has processed household waste between organic and inorganic waste which is supported by the Government's Berseri Program. Based on the results of a primary survey conducted using interviews and observations, people have processed household waste but have not processed rice washing waste water. This is because the waste water from washing rice is only used to water plants or is even thrown away directly. In fact, rice washing wastewater has the potential to be used for daily life such as liquid organic fertilizer, body care, natural cleaning of household furniture, livestock activities, and so on. Therefore, outreach was carried out to the people of Ngadilangkung Village to find out the potential of rice washing wastewater. Many people took part in the socialization and the people were quite active during the question and answer session. The results showed that as many as 20% of the people of RT 02 had used runoff water. So, it is hoped that the people of RT 02 RW 03 Ngadilangkung Village can create a sustainable environment by using rice washing waste water in their daily lives as an effort to reduce household waste.